(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1862)
Having read Commander Thomas’ description of the beehive houses in the previous volume, Dr Keller wrote to the Vice-President David Laing about similar structures found in the Swiss Alps. Although every structure of this type that the author has seen was ruined, he nonetheless concludes that they were used as dwellings based on their dimensions and situation.